1985
DOI: 10.1007/bf01321357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and application of continuity measures in primary care settings

Abstract: Continuity of contact between patients and physicians has become an important criterion of quality primary care. Using three measures of continuity that have appeared in the literature, this article examines, through the use of simulated data and through application to data from five primary care settings, the differences and utility of these approaches for measuring continuity. Further, these measures are applied to four selected diagnoses from each of the five sites, and the observed continuity scores afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Continuity of care was measured with 3 commonly used indices 19,41 : most frequent provider continuity (MFPC), 42 modified, modified continuity index (MMCI), 27,43 and continuity-of-care index (COC) 44 (Sup- 27 and COC integrates both aspects into a single metric. The primary outcome of the study was all-cause mortality.…”
Section: Data Sources and Measuresmentioning
confidence: 99%
“…Continuity of care was measured with 3 commonly used indices 19,41 : most frequent provider continuity (MFPC), 42 modified, modified continuity index (MMCI), 27,43 and continuity-of-care index (COC) 44 (Sup- 27 and COC integrates both aspects into a single metric. The primary outcome of the study was all-cause mortality.…”
Section: Data Sources and Measuresmentioning
confidence: 99%
“…Fortunately, empirical studies have shown that, at an organisational level, these different measures tend to give results that are highly correlated. 29,30 However, they do have different mathematical properties that can be important in some situations. In particular, continuity scores using some measures will tend to be inversely related to consultation rate, while other measures make adjustment for utilisation level.…”
Section: Which Measure?mentioning
confidence: 99%
“…In particular, continuity scores using some measures will tend to be inversely related to consultation rate, while other measures make adjustment for utilisation level. 29,30 How should data be collected?…”
Section: Which Measure?mentioning
confidence: 99%
“…One was the Most Frequent Provider Continuity Index (MFPC), which required first identifying the segment with the highest frequency of visits during the year, then calculating the fraction of total visits to that particular segment [35,36]. The higher the fraction, the more concentrated visits are to the dominant segment.…”
Section: Methodsmentioning
confidence: 99%